The Effect of Manure Dosage and Types of Plant Growth Regulators (PGRs) on the Generative Phase of Bird’s Eye Chili (Capsicum frutescens L) - Putri Rizkia; Hilda Pratiwi; Mizan Maulana (Journal of International Multidisciplinary Research, 2026)
This study aims to determine the effect of manure dosage and types of plant growth regulators (PGRs), as well as their interaction, on the generative phase of bird’s eye chili plants (Capsicum frutescens L.) in order to improve productivity, which remains fluctuating due to suboptimal cultivation practices. The research was conducted from February to March 2026 at the experimental field of the Pusat Riset Bisnis Kopbun Suka Tani Sejahtera, Kota Juang District, Bireuen Regency, using a factorial Randomized Block Design (RBD) of 4 × 3 with three replications. The first factor was the dosage of manure (control, 1 kg/plant, 1.5 kg/plant, and 2 kg/plant), while the second factor was the type of natural PGR (onion extract, rice water, and coconut water). Data were collected through direct observations on several parameters, including number of fruits, fruit weight, fresh biomass weight, root fresh weight, and root length, and were then analyzed to determine the effects of treatments and their interactions.          The results showed that certain doses of manure had a significant effect on increasing yield and root growth, while natural PGRs were able to enhance flowering, reduce flower drop, and accelerate fruit formation. The interaction between both treatments indicated that the optimal combination produced higher results compared to single treatments. The novelty of this study lies in the use of a combination of manure and natural PGRs based on local materials as a strategy to improve the generative phase. The implications of this research are expected to serve as a scientific reference for the development of sustainable cultivation techniques, as well as learning material and further research in the fields of agronomy and horticulture.